2009
DOI: 10.2304/eerj.2009.8.1.89
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Look at Spanish Scientific Publishing in the Framework of International Standards

Abstract: Research has become a key element in the knowledge-based society with its role of producing and disseminating results. In this context, scientific publishing becomes the means by which research activity and knowledge production are circulated to the scientific community and society at large. However, there are factors influencing the system of scientific publications in every national community or country that have to be taken into consideration. The author discusses the effects of the Spanish research system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The author also referred to other studies that found that factors, such as lack of incentives, language proficiency, international recognition and unfamiliarity with publishing systems, make researchers disuse these journals. Hence, it was concluded that the higher education system needs to be reformed and new standards need to be adopted to encourage scholars to publish internationally (Kindelan, 2009;L opez-Navarro et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author also referred to other studies that found that factors, such as lack of incentives, language proficiency, international recognition and unfamiliarity with publishing systems, make researchers disuse these journals. Hence, it was concluded that the higher education system needs to be reformed and new standards need to be adopted to encourage scholars to publish internationally (Kindelan, 2009;L opez-Navarro et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dominance of English in academe and the pressure to publish in top-tier journals is widely accepted internationally as the norm for researchers needing to engage in scholarly communication (Gea-Valor et al, 2014;Kindelan, 2009). These publications also add prestige to the research and is essential to career performance and trajectory, especially those seeking promotion and tenure (Flowerdew, 2008;Lillis and Curry, 2010).…”
Section: Challenge 3: Publicationmentioning
confidence: 99%
“…Another challenge is to avoid procrastination by favoring a predisposition to write about research results [1]. Furthermore, in non-English speaking countries students have to familiarize themselves with the rhetorical characteristics of a foreign language [7] and to assimilate different ways of defining and understanding problems [8].…”
Section: Introductionmentioning
confidence: 99%